2021
DOI: 10.1021/acs.nanolett.1c00890
|View full text |Cite
|
Sign up to set email alerts
|

Kinetically Controlled Self-Assembly of Binary Polymer-Grafted Nanocrystals into Ordered Superstructures via Solvent Vapor Annealing

Abstract: Polymer-inorganic nanocomposites based on polymer-grafted nanocrystals (PGNCs) are enabling technologically relevant applications owing to their unique physical, chemical, and mechanical properties. While diverse PGNC superstructures have been realized through evaporation-driven self-assembly, this approach presents multifaceted challenges in experimentally probing and controlling assembly kinetics. Here, we report kinetically controlled assembly of binary superstructures from a homogeneous disordered PGNC mix… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 50 publications
0
22
0
Order By: Relevance
“…Pentaethylenehexamine-terminated polystyrene (PS–PEHA) ligands were synthesized in a two-step reaction. In the first step, bromine-terminated polystyrene was synthesized by using activators regenerated by electron transfer atom transfer radical polymerization (ARGET ATRP). , In the second step, the bromine end group was converted to PEHA. Two grafting-to methods, namely, direct ligand-exchange and two-step ligand-exchange, were used to functionalize NCs with PS–PEHA ligands.…”
Section: Methodsmentioning
confidence: 99%
“…Pentaethylenehexamine-terminated polystyrene (PS–PEHA) ligands were synthesized in a two-step reaction. In the first step, bromine-terminated polystyrene was synthesized by using activators regenerated by electron transfer atom transfer radical polymerization (ARGET ATRP). , In the second step, the bromine end group was converted to PEHA. Two grafting-to methods, namely, direct ligand-exchange and two-step ligand-exchange, were used to functionalize NCs with PS–PEHA ligands.…”
Section: Methodsmentioning
confidence: 99%
“…PS-PEHA was synthesized in house according to our previously reported method. [71] To functionalized copper NRs with PS-PEHA, 20 mg of 5.6 k PS-PEHA was dissolved in 1.6 mL of anhydrous THF, to which 0.5 mL of copper NR solution (5 mg mL À1 in toluene) was added. The solution was sonicated for 10 s and was left undisturbed for 12 h inside a glovebox.…”
Section: Methodsmentioning
confidence: 99%
“…However, when the surface of Ag nanocrystals is coated by a layer of oleylamine, an inverse size dependence in surface plasmonic resonance was found, which clearly demonstrated that these coating molecules could modulate the nanocrystal electron oscillating frequency by changing the density of the electrons and the size and shape of electron distributions. ,, To date, small surfactant molecules with thiol, amine, or carboxylic acid polar groups have been frequently used to coat Ag nanocrystals, and the effect of these polar head groups on the LSPR properties of Ag nanocrystals has been intensively investigated . A variety of polymers with specific terminal groups have been grafted from/to nanocrystals to further diversify the surface modifications of nanocrystals. In comparison with small surfactant molecules, the chain length of the polymers can be freely controlled in a broad range from a few nanometers to tens of nanometers, which enables control of the thickness of the surface coating layer on nanocrystals with high precision. Consequently, polymers coated on nanocrystals can be used to control the spacing between two neighboring nanocrystals in the solid state, which is considered to be pivotal in determining the electronic coupling between nanocrystals.…”
Section: Introductionmentioning
confidence: 99%